ПОСЛАННЯ МИТРОПОЛИТА МИХАЇЛА (ЄРМАКОВА) ДО ДУХОВЕНСТВА ТА ВІРУЮЧИХ УКРАЇНИ ВІД 17 ЛИСТОПАДА 1927 Р. (Zaporizhzhia Historical Review, 2021)
Author includes to scientific application unknown earlier text – Message from exarch Michael (Ermakov) to clergy and believers of 17 November 1927, explaining causes, which were coursed appearance of this document, commenting on its basic idea and underlining its social resonance.